2020
DOI: 10.1371/journal.pone.0229940
|View full text |Cite
|
Sign up to set email alerts
|

Preventability of unplanned readmissions within 30 days of discharge. A cross-sectional, single-center study

Abstract: Objectives To identify the preventability, determinants and causes of unplanned hospital readmissions within 30 days of discharge using a multidisciplinary approach and including patients' perspectives. Design A prospective cross-sectional single-center study. Setting Urban teaching hospital in Amsterdam, the Netherlands. Participants 430 patients were included. Inclusion criteria were: age � 18 years, discharged from one of seven participating clinical departments and an unplanned readmission within 30 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The data for this study were collected within the context of a larger study on all-cause readmissions (van der Does et al, 2020). The all-cause study and the current study used the same inclusion criteria.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data for this study were collected within the context of a larger study on all-cause readmissions (van der Does et al, 2020). The all-cause study and the current study used the same inclusion criteria.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…All seven clinical departments and the hospital pharmacy assigned a resident to review readmissions. All residents received a group training prior to the start of the study regarding the assessment whether the readmission was caused by healthcare (i.e., causality) and the preventability of readmissions (van der Does et al, 2020). In case of replacement of a resident, the new resident received the same training.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study methodology has been published before; however, the previous study primarily focused on the method of assessing preventability and analyzed the causes of PPRs in a smaller cohort of patients 9 . In summary, to distinguish between PPR and non-PPR, the readmissions were manually reviewed by physicians and pharmacists in 2 phases.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review has identified median PPR rates of 27.1% of all readmissions, with a broad range varying from 5 to 79% 8 . Previous studies explored different mechanisms leading to PPRs, including management-related, medication-related, and diagnostics-related causes 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%